1996
DOI: 10.1300/j087v24n03_01
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of African American Children's Cognitive and Emotional Reactions to Parental Separation

Abstract: The present study surveyed 76 black American third through sixth graders who had experienced a parental separation. Children's problematic beliefs about separation were sigdicantly and positively related to teacher reported problem behavior (r = .30, p = .01). Post hoc analyses suggested that children who blame themselves seem to have particular difficulty adjusting to the separation. Children who had more positive reactions to the separation were more empathic (r = .22, p = .05). Finally, the recency of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…Presumably, escape from a high‐conflict marriage benefits children because it removes them from an aversive, stressful home environment. In contrast, a divorce that is not preceded by a prolonged period of overt discord may represent an unexpected, unwelcome, and uncontrollable event, an event that children are likely to experience as stressful (Amato, 1987; Bussell, 1995; Duran‐Aydintug, 1997; Grych & Finchan, 1990; Healy et al, 1993; Jacobson, 1978; Kim et al, 1997). Divorce under these circumstances represents a major change in what may otherwise have been a secure and (from a child's perspective) seemingly well‐functioning family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, escape from a high‐conflict marriage benefits children because it removes them from an aversive, stressful home environment. In contrast, a divorce that is not preceded by a prolonged period of overt discord may represent an unexpected, unwelcome, and uncontrollable event, an event that children are likely to experience as stressful (Amato, 1987; Bussell, 1995; Duran‐Aydintug, 1997; Grych & Finchan, 1990; Healy et al, 1993; Jacobson, 1978; Kim et al, 1997). Divorce under these circumstances represents a major change in what may otherwise have been a secure and (from a child's perspective) seemingly well‐functioning family.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that children who place the blame for the divorce on themselves tend to be more poorly adjusted (Bussell, 1995). Healy, Steward, and Copeland (1993) studied primary school children 6 months after parental separation and found that one third reported some feelings of self‐blame.…”
Section: Studymentioning
confidence: 99%
“…As the largest Latino subgroup, MAs were selected to circumvent problems associated with ethnic glossing, when the various Latino subgroups are combined and assumed to be equivalent. Research has shown that divorce is associated with increased risk of academic and externalization problems for AA children (Bussell, 1995; Jenkins & Guibubaldi, 1997) and psychological problems, marital problems, and poor educational attainment in adulthood (Amato & Keith, 1991b). Research has also shown that parental divorce is associated with poorer academic achievement and delayed young adult developmental task attainment among Latinos (Battle, 1997; Johnson & McNeil, 1998).…”
Section: Nbp: Steps From Efficacy To Effective Implementation In the mentioning
confidence: 99%
“…As the largest Latino subgroup, MAs were selected to circumvent problems associated with ethnic glossing, when the various Latino subgroups are combined and assumed to be equivalent. Research has shown that divorce is associated with increased risk of academic and externalizing problems for AA children (Bussell, 1995; Jenkins & Guidubaldi, 1997). Similarly, parental divorce is associated with poor academic achievement among Latinos (Battle, 1997) and a range of mental health problems (including externalizing and internalizing problems), substance use, low academic achievement and low self-esteem among Asian and Asian American children and adolescents (e.g., Sun & Li, 2007).…”
Section: Step 4: Adapting the Nbp To Meet The Needs Of The Populationmentioning
confidence: 99%